Sustainable management of NHS assets backlog maintenance. Issue 5 (7th November 2016) - Pantzartzis, Efthimia; Deka, Lipika; Price, Andrew D.F.; Tann, Chris; Mills, Grant R.W.; Rich-Mahadkar, Sameedha
Abstract : Purpose: Lord Carter's (2015) "Review of Operational Productivity in NHS providers" stated that to improve National Health Service (NHS) England's efficiency, operational productivity should be targeted in four main areas, one being estates management. NHS England's estate includes a variety of buildings some of which are considered no longer fit-for-purpose, thus creating risk to patients and staff. These built assets require continuous maintenance, adding pressures to NHS England's precarious financial situation. The purpose of this paper is to identify positive strategies and major constraints to achieving sustainable management of backlog maintenance (BM) across the NHS assets, and thus suggest balanced actions. Design/methodology/approach: The research adopts a qualitative approach and combines: literature review of current BM methodologies; interviews with estates and facilities directors from seven NHS trusts on BM strategies; and a NHS trust detailed case study. Findings: The major finding is that sustainable management of BM is achievable if there is a consistent, pro-active and long-term strategic approach where critical levels of BM are prioritised. Additional issues (i.e. appropriate methodology, performance metrics and links with clinical service delivery strategies) also need to be considered. Practical implications: This study is relevant to the management of the NHS estate including development and adoption of sustainable strategies. Originality/value: This paper offers original insights to the factors influencing healthcare estates' BM at a time when the UK policy agenda is targeting infrastructure operational efficiency and organisations are seeking more comprehensive methodologies.